Measuring women’s empowerment in agriculture: Innovations and evidence - Quisumbing, Agnes R.; Cole, Steven M.; Elias, Marlène; Faas, Simone; Galiè, Alessandra; Malapit, Hazel J.; Meinzen-Dick, Ruth S.; Myers, Emily; Seymour, Greg; Twyman, Jennifer (Elsevier, 2023)
This paper addresses women's empowerment in agriculture, innovations in its measurement, and emerging evidence. We discuss the evolution of the conceptualization and measurement of women's empowerment and gender equality since 2010. Using a gender and food systems framework and a standardized measure of women's empowerment, the Women's Empowerment in Agriculture Index (WEAI), we review the evidence on “what works” to empower women based on impact evaluations of a portfolio of 11 agricultural development projects with empowerment objectives and a scoping review of livestock interventions. We then review the evidence on associations between empowering women and societal benefits--agricultural productivity, incomes, and food security and nutrition. We conclude with recommendations for measurement and policy.